3D structure design and simulation for efficient particles capture: The influence of nanofiber diameter and distribution. (June 2020) - Wu, Jiajun; Akampumuza, Obed; Liu, Penghong; Quan, Zhenzhen; Zhang, Hongnan; Qin, Xiaohong; Wang, Rongwu; Yu, Jianyong
Graphical abstract: Highlights: 3D filter structures design with different nanofiber diameter and distribution. Simulation of filters with high filtration efficiency and low pressure drop. Experimental verification of simulated results on filtration effect. Abstract: Software simulation is a convenient and efficient way to design and check different air filter structures with high efficiency and low pressure drop. In this work, nanofiber filters of different diameters ranging from 100 to 900 nm were designed to check their influence on filtration efficiency, pressure drop and quality factor ( QF ). Slip-flow effect of air molecules was considered on the surface of single fiber. Then, filters with different diameter distributions were constructed to study the filtration efficiency discrepancy when the filter thickness and porosity were kept equal. With a rotation of the filters composed of nanofibers of 500 nm in diameter in the computational domain, the filtration efficiency and QF increased steadily. The simulation results were partially verified by electrospun cellulose acetate nanofiber filter, and meanwhile provide with new insights into the filter structure design of high filtration efficiency with low pressure drop.